Penyuluhan dan Pelatihan Ramuan Untuk Meningkatkan Daya Tahan Tubuh - Indri Kusuma Dewi; Aldora Salwa Salsabila; Anisa Alfi Mahmudah; Corry Ervadilla Widiarsari; Farah Salsabila A’isyi; Ghoffarida Alkogajeva; Larissa Amanda (Jurnal Empathy Pengabdian Kepada Masyarakat, 2022)
Background: Indonesia ranks 14th with COVID-19 cases in the world. The immune system could be a bulwark against COVID-19. Exercise, balanced nutrition, and herbal deformity is way to maintain and improve the work of the immune system. The immune system could be increase with a potential of ginger, turmeric, lime, and galangal. This training aims to train mothers of family empowerment and welfare in RT 02/RW 09 Danguran Village about traditional ingredients to increase endurance. Methods: Training on immune-enhancing ingredients to mothers of family empowerment and welfare by Pharmacy students from the Health Polytechnic of the Ministry of Health of Surakarta on Friday 11 February 2022 at RT 02/RW 09, Danguran Village, South Klaten, and a T-test was carried out with the result of pretest and post test. Results: The pre-test result was 84.23% and the post-test was 95.38% with the t-test result was 0.02. These results indicate a significant change in knowledge between before and after being given training because t-count <0.05. Conclusion: There is an increase in the knowledge of mothers of family empowerment and welfare RT 02/ RW 09 Danguran Village about traditional ingredients to increase endurance.